1997
DOI: 10.1002/pro.5560060320
|View full text |Cite
|
Sign up to set email alerts
|

Folding propensities of peptide fragments of myoglobin

Abstract: Myoglobin has been studied extensively as a paradigm for protein folding. As part of an ongoing study of potential folding initiation sites in myoglobin, we have synthesized a series of peptides covering the entire sequence of sperm whale myoglobin. We report here on the conformational preferences of a series of peptides that cover the region from the A helix to the FG turn. Structural propensities were determined using circular dichroism and nuclear magnetic resonance spectroscopy in aqueous solution, trifluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
82
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 46 publications
11
82
1
1
Order By: Relevance
“…of native contacts (tertiary structure), with the correlation coefficient of 0.94. Thus, as far as the correlation between the formation of the secondary structures and the completion of the tertiary structure is concerned the present folding model is consistent with both computational 3,4 and experimental 43 results. The current study also agrees with the computational work by Duan et al, 3 where it is shown that the burst phase precedes the slow conformational readjustment phase in HP-36 folding.…”
Section: Discussion On Folding Mechanismsupporting
confidence: 86%
See 2 more Smart Citations
“…of native contacts (tertiary structure), with the correlation coefficient of 0.94. Thus, as far as the correlation between the formation of the secondary structures and the completion of the tertiary structure is concerned the present folding model is consistent with both computational 3,4 and experimental 43 results. The current study also agrees with the computational work by Duan et al, 3 where it is shown that the burst phase precedes the slow conformational readjustment phase in HP-36 folding.…”
Section: Discussion On Folding Mechanismsupporting
confidence: 86%
“…This observation that the secondary structure is formed in the presence of partial tertiary structure, is consistent with experimental observation. 43 ADMD pathway for HP-36 is consistent with the hydrophobic collapse model 44 in that the tertiary and secondary structures are formed concurrently after the initial hydrophobic collapse. After the collapse (i.e., j > 950), we find a good correlation between the number of native hydrogen bonds (secondary structure) and the number Figure 6.…”
Section: Discussion On Folding Mechanismsupporting
confidence: 67%
See 1 more Smart Citation
“…Studies of isolated peptide fragments of apomyoglobin indicate that the H helix possesses the highest propensity for spontaneous formation of helical structure in aqueous solution, whereas the fragments corresponding to the G helix possess poor helix propensity in isolation (24,25). Both the G and A helices show extensive helix formation in longer peptides where interhelix contacts are possible (26). These data clearly show the importance of tertiary interactions for folding of the A and G helices.…”
mentioning
confidence: 88%
“…To further this understanding, the kinetic aspects of the folding of apomyoglobin have been the subject of considerable experimental study (Hughson et al, 1990(Hughson et al, , 1991Jennings & Wright, 1993; Shin et al, 1993a Shin et al, , 1993bWaltho et al, 1993;Jennings et al, 1994;Eliezer et al, 1995; Loh et al, 1995;Ballew et al, 1996;Reymond et al, 1997). Elucidating the kinetic aspects of folding requires information on how the peptide elements that make up the protein interact dynamically to produce the native folding pattern.…”
Section: Abstract: Apomyoglobin; Diffusion-collision Model; Folding Kmentioning
confidence: 99%